(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: We report a case of stepwise amplification of drug resistance to the new drug - Bedaquiline in a tuberculosis (TB) patient previously assessed as having completed treatment, with the hope of sharing information to improve the quality of treatment monitoring. Case report: A 58-year-old male patient with a history of two previous TB treatments was assessed as “complete”. Initially a case of drug-sensitive TB, the patient was found to have developed stepwise resistance to Rifampicin, Fluoroquinolones and especially the new drug “Bedaquiline”. Discussion: Although there was no evidence of bacterial genome sequencing to exclude the possibility of infection with new strains, or heteroresistance; this case still points towards the possibility of acquired drug resistance due to no history of contact with a drug-resistant TB patient or use of second-line drugs idientified; meanwhile, the patient lacked compliance and re-examination in the final stage of treatment to have sufficient evidence for accurate treatment outcome assessment. Conclusion: Vietnam needs solutions to improve the quality of treatment monitoring, re-examination during treatment, and monitoring TB patients after completing treatment to promptly detect and treat cases of relapse with drug resistance amplification. Keywords: Drug-resistant tuberculosis, Bedaquiline resistance, drug susceptibility testing, treatment monitoring, treatment completion